HIV Infection and Persistence in Pulmonary Mucosal Double Negative T Cells In Vivo - Meziane, Oussama (J Virol, 2020)
The lungs are relatively unexplored anatomical human immunodeficiency virus (HIV) reservoirs in the antiretroviral therapy (ART) era. Double negative (DN) T cells are a subset of T cells that lack expression of CD4 and CD8 (CD4(−) CD8(−)) and may have both regulatory and effector functions during HIV infection. Notably, circulating DN T cells were previously described as cellular HIV reservoirs. Here, we undertook a thorough analysis of pulmonary versus blood DN T cells of people living with HIV (PLWH) under ART. Bronchoalveolar lavage (BAL) fluid and matched peripheral blood were collected from 35 PLWH on ART and 16 uninfected volunteers without respiratory symptoms. Both PLWH and HIV-negative (HIV(−)) adults displayed higher frequencies of DN T cells in BAL versus blood, and these cells mostly exhibited an effector memory phenotype. In PLWH, pulmonary mucosal DN T cells expressed higher levels of HLA-DR and several cellular markers associated with HIV persistence (CCR6, CXCR3, and PD-1) than blood. We also observed that DN T cells were less senescent (CD28(−) CD57(+)) and expressed less immunosuppressive ectonucleotidase (CD73/CD39), granzyme B, and perforin in the BAL fluid than in the blood of PLWH. Importantly, fluorescence-activated cell sorter (FACS)-sorted DN T cells from the BAL fluid of PLWH under suppressive ART harbored HIV DNA. Using the humanized bone marrow-liver-thymus (hu-BLT) mouse model of HIV infection, we observed higher infection frequencies of lung DN T cells than those of the blood and spleen in both early and late HIV infection. Overall, our findings show that HIV is seeded in pulmonary mucosal DN T cells early following infection and persists in these potential cellular HIV reservoirs even during long-term ART. IMPORTANCE Reservoirs of HIV during ART are the primary reasons why HIV/AIDS remains an incurable disease. Indeed, HIV remains latent and unreachable by antiretrovirals in cellular and anatomical sanctuaries, preventing its eradication. The lungs have received very little attention compared to other anatomical reservoirs despite being immunological effector sites exhibiting characteristics ideal for HIV persistence. Furthermore, PLWH suffer from a high burden of pulmonary non-opportunistic infections, suggesting impaired pulmonary immunity despite ART. Meanwhile, various immune cell populations have been proposed to be cellular reservoirs in blood, including CD4(−) CD8(−) DN T cells, a subset that may originate from CD4 downregulation by HIV proteins. The present study aims to describe DN T cells in human and humanized mice lungs in relation to intrapulmonary HIV burden. The characterization of DN T cells as cellular HIV reservoirs and the lungs as an anatomical HIV reservoir will contribute to the development of targeted HIV eradication strategies.